Pengaruh Audit Capacity Stress, Auditor Spesialisasi Industri, Komite Audit, dan Alignment Effect terhadap Kualitas Audit - Zunita, Liya; Khikmah, Siti Noor; Mranani, Muji (Universitas Muhammadiyah Magelang, 2022)
This study aims to examine and analyze the effect of audit capacity stress, auditor industry specialization, audit committee and alignment effect on audit quality. The population data used in this study is the annual report of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 with purposive sampling method. Based on predetermined criteria, 129 samples were obtained from total 43 companies during 3 year research period. This research uses SPSS 25 analysis tool with logistic regression analysis. The results showed that audit capacity stress, industry specialization auditor, and audit committee had a positive effect on audit quality, while the alignment effect had no effect on audit quality.